2022
DOI: 10.1002/ppap.202200134
|View full text |Cite
|
Sign up to set email alerts
|

Plasma‐electrified postharvest preservation of Citrus sinensis: Process technology and freshness‐keeping and anticorrosion effects

Abstract: Nitrogen oxide-generating dielectric barrier discharge plasma is shown to effectively inhibit microorganisms and maintain fruit freshness. Physical and biological mechanisms of the plasma-electrified fungicidal effects suggest that plasma-generated NO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Atmospheric pressure non-thermal plasmas have expressed broad prospects in many fields because of their remarkable chemical activity achieved at a gas temperature near room temperature [1][2][3][4][5]. In some specific areas such as water purification and plasma activated water preparation, the plasmas inevitably come into contact with the liquid [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Atmospheric pressure non-thermal plasmas have expressed broad prospects in many fields because of their remarkable chemical activity achieved at a gas temperature near room temperature [1][2][3][4][5]. In some specific areas such as water purification and plasma activated water preparation, the plasmas inevitably come into contact with the liquid [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, the application of ARTP to organisms has been more about lethal damage and the inactivation of organisms. [74][75][76] In recent years, an increasing number of researchers have found that sublethal effects on cells can be achieved by controlling the power and treatment time of ARTP, 11 and beyond a certain range, lethal effects can occur, thus extending the application of biological mutagenesis. 77,78 The different biological effects resulting from the interaction between ARTP and organisms are achieved through a series of complex reactive processes.…”
Section: Artp Mutagenesis Mechanismmentioning
confidence: 99%
“…Nitrous oxide (N 2 O), which is also known as laughing gas, exerts a mild anesthetic effect that reduces pain; thus, it is typically used in dentistry and minor surgeries [13,14]. Peroxynitrous acid (ONOOH), which is a strong oxidant and nitrating agent, is crucial in the antibacterial defense of organisms and can traverse biological membranes to damage cellular components owing to its significant cytotoxicity, thereby inducing the death of harmful cells [15,16].…”
Section: Introductionmentioning
confidence: 99%